Determinasi Kinerja Keuangan di Perusahaan Sektor Property & Real Estate Periode 2019-2023 - Anandyaningsih Risnika Putri; Almira Santi Samasta; Vicky Oktavia; Suhita Whini Setyahuni (MANAJEMEN, 2025)
This study's goal is to ascertain the connection between liquidity ratio (CR), asset management (TATO), capital structure (DAR) and firm size on financial performance, The property & real estate firms that were listed between 2019 and 2023 on the Indonesia Stock Exchange (IDX). The study's sample, which was 52 companies in a period of (5) periods with a total of 260 data. The multiple regression analysis is used in this study method with the type of panel data with the Random Effect Model (REM) method. According to the study's findings that asset management has a favorably and significantly effect on financial performance, capital structure has a negatively and significantly effect on financial performance, but liquidity ratio and firm size have no effect on financial performance.